PENGEMBANGAN MODEL PEMBELAJARAN IPA BERBASIS 4N (NENG, NING, NUNG, NANG) UNTUK MENCIPTAKAN PROSES BELAJAR FUNGSIONAL PESERTA DIDIK SMP - Fuadah, Ainun; Djohar, Djohar (Jurnal Inovasi Pendidikan IPA, 2015)
The aims of this study are (1) to develop 4N concept from Ki Hajar Dewantara into 4N model of learning for science, (2) to investigate the quality of developed products, (3) to investigate the effect of 4N learning model for scinece learning to Tri Nga competencies, and (4) to investigate the implementation of the model.The study used 9 steps of research and development (R&D) model of Borg & Gall without taking the dissemination process.The results of the study are as follows. (1) The 4N concept was developed to become 4N model for science learning. (2) The Products are appropriate to use for teaching and learning process. (3) The 4N learning model can achieve a functional science learning: (a) the model can increase Tri Nga competencies. (b) Science learning using the 4N model achieves the KKM target, and (c) the 4N model gets good response from the students. (4) The 4N model is in well done category. Key words: learning model, 4N (neng-ning-nung-nang) concept, functional learning.